(untitled) (Journal of the College of Education for Women, 2019)
In this paper, a method for hiding cipher text in an image file is introduced . Theproposed method is to hide the cipher text message in the frequency domain of the image.This method contained two phases: the first is embedding phase and the second is extractionphase. In the embedding phase the image is transformed from time domain to frequencydomain using discrete wavelet decomposition technique (Haar). The text message encryptedusing RSA algorithm; then Least Significant Bit (LSB) algorithm used to hide secret messagein high frequency. The proposed method is tested in different images and showed success inhiding information according to the Peak Signal to Noise Ratio (PSNR) measure of the theoriginal image .